Nasolabial cyst: Clinical presentation and surgical outcome of 14 cases with literature review - Gurung, U; Tamang, N; Tripathi, P (Journal of Institute of Medicine Nepal, 2024)
Introduction: Nasolabial cyst is a rare, developmental, non-odontogenic cyst in the nasal alar region. The study aimed to assess the clinical characteristics, intra-operative findings, complications and recurrence following sublabial excision of nasolabial cyst and review the related literature.Methods: It was a retrospective chart review of 14 cases of nasolabial cysts who underwent excision via sublabial approach in a tertiary center from December 2014 to May 2017. The data on clinical characteristics, intra-operative findings, complications and recurrence were assessed.Results: Fourteen patients consisted of 9 females and 5 males. The age ranged from 22 to 73 years. Alar fullness was common presentation for all while 3 patients had associated pain. Two patients noted nasal obstruction. The cyst was located on left in 8 and on right side in 6 patients. The size ranged from 1.5 x1.5 to 4 x 4 cm2. All patients had the cyst excised totally via sublabial approach. Post-operatively, 8 patients developed cheek swelling which subsided within 2 weeks. None of the patients had gingival or tooth numbness or wound gape. There was no recurrence noted in follow up ranging from 3 to 30 months.Conclusions: Nasolabial cyst is a slow growing, unilateral cyst in the nasal alar region, common in female in the fourth and fifth decade. Sublabial excision is the standard treatment with no recurrence however it has risk of intra-operative rupture of cyst and complications like cheek swelling, bruising, facial pain, facial numbness, numbness of teeth or gingiva. Transnasal endoscopic marsupialization is a new treatment modality.